Research Activities of the Economic and Research Branch of the Canadian Department of Labor - Saunders, George (Relations industrielles / Industrial Relations, 1966)
The author is surveying the activities of the Economic and Research Branch in the Department of Labour (Ottawa). Collecting and analysing statistical series in the labor field are the most important ones. In-depth research projects are concerned with relationships between labor data and other related economic variables.